Heterotophic Growth of Ankistrodesmus Sp. for Lipid Production Using Cassava Starch Hydrolysate as a Carbon Source - Salim, Mohamad Agus (The International Journal of Biotechnology, 2013)
Research has been done on the culture of Ankistrodesmus sp. through heterotrophic conditions to obtain lipid content. Heterotrophic culture with the addition of several concentrations of cassava starch hydrolysate (CSH) as a source of organic carbon that increased lipid content. The highest cell density and cell growth rate (cell division) of Ankistrodesmussp achieved at 10 g.l-1 of CSH concentration on 2.46 x 106 cells.ml-1 which occurred at the 8th day and 0.50 cells.day-1 respectively. While the highest biomass and lipid content achieved at 5 g.l-1 of CSH concentration on 0.94 g.l-1 and 26% respectively.